Myanmar Agricultural Performance Survey (Monsoon 2022): Farm commercialization - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
This Research Note presents the results from an assessment of farm commercialization in Myanmar after the monsoon of 2022, based on data from a phone survey – the Myanmar Agriculture Performance Survey (MAPS) – that was conducted with almost 5,000 crop farmers in all states/regions of the country, over the period February – March 2023. It is found that: